EFEKTIVITAS PROGRESSIVE MUSCLE RELAXATION(PMR)DAN GUIDED IMAGERY (GI)TERHADAP KEJADIAN MUAL MUNTAH PADA PASIEN KANKER YANG MENJALANI KEMOTERAPI DI RUMAH SAKIT REGIONAL WILAYAH INDONESIA TIMUR - Idha Nurwahidah (Stikes Graha Edukasi Makassar, 2018)
Introduction: One of the best choices of treatments for cancer nowadays is chemotherapy.However, it has many side effects affecting physical and psychological condition of patient. One of the side effects is nausea and vomit. Beside pharmacological interventions, nausea and vomit can be treated with complementary therapy such as progressive muscle relaxation (PMR) andguided imagery (GI). This study aims to determine the effect of PMR and GI on nausea and vomit score for cancer patients undergoing chemotherapy. Method: Sample used in this study were 11 patients undergoing chemotherapy at L1AD in Dr. Wahidin Sudirohusodo hospitals, Makassar with consecutive sampling as non probability sampling technique. Result:This study showed that there was a different scores of nausea and vomit between pre and post intervention of PMR and GI (p = 0.0001).Conclusions: PMR and GI have effect significantly on decreasing of nausea and vomit to the patients of cancer undergoing chemotherapy